Characterization of G protein‐coupled estrogen receptors in Japanese medaka, Oryzias latipes. Issue 9 (17th December 2020) - Miyaoku, Kaori; Ogino, Yukiko; Lange, Anke; Ono, Ayaka; Kobayashi, Tohru; Ihara, Masaru; Tanaka, Hiroaki; Toyota, Kenji; Akashi, Hiroshi; Yamagishi, Genki; Sato, Tomomi; Tyler, Charles R.; et al.
Abstract: The G protein‐coupled estrogen receptor 1 (Gper1) is a membrane‐bound estrogen receptor that mediates non‐genomic action of estrogens. A Gper1‐mediating pathway has been implicated in reproductive activities in fish, including oocyte growth, but Gper1 has been characterized in only a very limited number of fish species. In this study, we cloned and characterized two genes encoding medaka ( Oryzias latipes ) Gper1s, namely, Gper1a and Gper1b, and phylogenic and synteny analyses suggest that these genes originate through a teleost‐specific whole genome duplication event. We found that Gper1a induced phosphorylation of mitogen‐activated protein kinase (MAPK) in 293T cells transfected with medaka Gper1s on exposure to the natural estrogen, 17β‐estradiol (E2) and a synthetic Gper1 agonist (G‐1), and treatment with both E2 and G‐1 also decreased the rate of spontaneous maturation in medaka oocytes. These findings show that the processes for oocyte growth and maturation are sensitive to estrogens and are possibly mediated through Gper1a in medaka. We also show that 17α‐ethinylestradiol (EE2), one of the most potent estrogenic endocrine‐disrupting chemicals, and bisphenol A (BPA, a weak environmental estrogen) augmented phosphorylation of MAPK through medaka Gper1s in 293T cells. Interestingly, however, treatment with EE2 or BPA did not attenuate maturation of medaka oocytes. Our findings support that Gper1‐mediated effects on oocytes are conserved among fish species, but effects of estrogenic endocrine‐disrupting chemicals on oocytes acting through Gper1 may be divergent among fish species. Abstract : We cloned and characterized medaka Gper1a and Gper1b, which encode membrane‐bound estrogen receptors. Gper1a induced phosphorylation of MAPK in 293T cells transfected with medaka Gper1s on exposure to 17β‐estradiol (E2) and G‐1, and treatment with both E2 and G‐1 also decreased the rate of spontaneous maturation in medaka oocytes. Estrogenic endocrine‐disrupting chemicals, such as 17α‐ethinylestradiol and bisphenol A, also, at least in part, activated MAPK. The current results provide advance understanding on the membrane‐bound estrogen receptor in fish.